Proceedings of the 2015 ACM International Joint Conference on Pervasive and Ubiquitous Computing 2015
DOI: 10.1145/2750858.2806064
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes toward vehicle-based sensing and recording

Abstract: Vehicles increasingly include features that rely on hi-tech sensors and recording; however, little is known of public attitudes toward such recording. We use two studies, an online survey (n=349) and an interview-based study (n=15), to examine perceptions of vehicle-based sensing and recording. We focus on: 1) how vehicle-based recording and sensing may differ from perceptions of current recording; 2) factors that impact comfort with vehicle-based recording for hypothetical drivers versus bystanders; and 3) pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Researchers found that different contexts overlapping can produce new concerns [37]. Other studies have investigated bystanders' concerns with smart devices to examine the influence of contextual factors (i.e., purposes, mechanisms, and bystanders' ability to control data collection) [45,61,89,90,90,92,96,97].…”
Section: Bystander Privacy Concerns With the Smart-homementioning
confidence: 99%
“…Researchers found that different contexts overlapping can produce new concerns [37]. Other studies have investigated bystanders' concerns with smart devices to examine the influence of contextual factors (i.e., purposes, mechanisms, and bystanders' ability to control data collection) [45,61,89,90,90,92,96,97].…”
Section: Bystander Privacy Concerns With the Smart-homementioning
confidence: 99%
“…It has been shown that various dimensions affect individuals' privacy and that culture-which could be considered at many levels, such as socio-cultural, political, or the individual level-can explain differences in privacy attitudes [45], [46]. Our research is based on vehicle dashcams, which have mobility and wider coverage in the real world and supports the generation of various data types (e.g., video, sound, and location), and hence motives and concerns will be different from existing research [29], [47].…”
Section: Information Privacy Concerns Across Different Nationsmentioning
confidence: 99%
“…Dashcams are relatively new recording devices, and though there is limited research directly related to dashcam video sharing context, increased research is being conducted related to vehicle-based sensor data [29], [30] and dashcam technology, such as anticipating accidents [31] or moving object detection algorithms in dashcam videos [32]. In this section, we briefly state the importance of vehicular sensing and recording, and its applications and then review prior studies regarding national differences in online information sharing, information privacy concerns, and traffic safety perceptions to discuss similarities and differences in terms of dashcam video sharing motives and concerns.…”
Section: Introductionmentioning
confidence: 99%